1993
DOI: 10.1093/arclin/8.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among academic, neuropsychological, and intellectual status in subtypes of adults with learning disability

Abstract: A study was conducted of 102 adults with learning disability for the purposes of (1) contrasting a rule-based with an empirical method of classification into subtypes based on academic achievement levels in reading and arithmetic; and (2) examining cognitive profiles obtained with the Luria-Nebraska Neuropsychological Battery and the Wechsler Adult Intelligence Scale-Revised (WAIS-R) associated with each of the rule and empirically based subtypes. Both similarities and differences were found between classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In the case of the students with LD, as expected, tests of language ability and psychomotor speed were the best discriminators between the subjects with LD and the controls. The present findings would confirm those of other studies showing that the cognitive characteristics of LD are not necessarily outgrown by adolescence, but may persist into adulthood (Goldstein, 1990;Goldstein et al, 1993;McCue & Goldstein, 1991;Spreen, 1987;Spreen & Haaf, 1986). These results also support the work of Reiff and deFur (1992) and others (Axelrod & Zvi, 1992;Cordoni et al, 1981;Morris & Walter, 1991), who studied college students in particular and found that students with LD continued to experience difficulties in selected academic areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the case of the students with LD, as expected, tests of language ability and psychomotor speed were the best discriminators between the subjects with LD and the controls. The present findings would confirm those of other studies showing that the cognitive characteristics of LD are not necessarily outgrown by adolescence, but may persist into adulthood (Goldstein, 1990;Goldstein et al, 1993;McCue & Goldstein, 1991;Spreen, 1987;Spreen & Haaf, 1986). These results also support the work of Reiff and deFur (1992) and others (Axelrod & Zvi, 1992;Cordoni et al, 1981;Morris & Walter, 1991), who studied college students in particular and found that students with LD continued to experience difficulties in selected academic areas.…”
Section: Discussionsupporting
confidence: 92%
“…The choice of the various tests reflects findings related to MHI (Kane, 1991;Miller, 1986) and LD (Goldstein, 1990;Goldstein, Katz, Slomka, & Kelly, 1993;McCue & Goldstein, 1991;Rourke, 1989). Because MHI research indicates that the deficits often increase as a function of task complexity or demand (e.g., Gulbrandsen, 1984), we selected relatively complex neuropsychological measures within each functional domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with acquired academic deficits (e.g., acquired alexia) were excluded. This sample was utilized in several other studies (Goldstein, Katz, Slomka, & Kelly, 1993;Katz, Goldstein, Rudisin, & Bailey, 1993) where more detail concerning the establishment of the diagnoses is provided. To summarize, all participants met both DSM-III-R and State of Pennsylvania Office of Vocational Rehabilitation requirements for an LD diagnosis.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Moving from ASD with a range of intellectual ability to focus exclusively on ID, Goldstein, Katz, Slomka, and Kelly (1993) derived three clusters from 102 sequential adult referrals for ID assessment/treatment (mean age 24.6 years). Referrals were all made for some form of employment support which, in conjunction with a mean IQ of 88 in the sample, again suggests relatively high functioning and a likely lack of generalizability.…”
Section: Identifying Needs-based Id Groupingsmentioning
confidence: 99%